1991
DOI: 10.1080/00914039108041082
|View full text |Cite
|
Sign up to set email alerts
|

Wood Flour and Polypropylene or High Density Polyethylene Composites: Influence of Maleated Polypropylene Concentration and Extrusion Temperature on Properties

Abstract: The effects of the concentration of a maleated polypropylene additive (0 to 5 percent by weight) and of extrusion blending temperature (190T to 250°C) on the mechanical properties of extruded and injection-molded polypropylene-wood flour composites were investigated. The effects of maleated polypropylene additive on similarly processed polypropylene-wood flour and high density polyethylenewood flour composites were also compared. Both the additive and the high extrusion temperature led to some wood degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 4 publications
2
29
1
Order By: Relevance
“…Others have shown that the flexural behavior of the composites can vary significantly with the type of filler and coupling agent employed. 10,31 LPC containing a combination of STDDGS with PWF showed superior mechanical properties (except elongation values) compared to LPC composed of only STDDGS (Figure 3). LPC composed of 12.5% STDDG and 12.5% PW (PP-12.5PW/12.5STDDGS-MAPP) exhibited u , E, %El, E b , and impact strength values that were +15%, +61%, À79%, +78%, and À36%, respectively, of the values obtained from neat PP.…”
Section: Influence Of Mixing Different Fillersmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have shown that the flexural behavior of the composites can vary significantly with the type of filler and coupling agent employed. 10,31 LPC containing a combination of STDDGS with PWF showed superior mechanical properties (except elongation values) compared to LPC composed of only STDDGS (Figure 3). LPC composed of 12.5% STDDG and 12.5% PW (PP-12.5PW/12.5STDDGS-MAPP) exhibited u , E, %El, E b , and impact strength values that were +15%, +61%, À79%, +78%, and À36%, respectively, of the values obtained from neat PP.…”
Section: Influence Of Mixing Different Fillersmentioning
confidence: 99%
“…10,19,26,27,[29][30][31] Coupling agents act as intermediates to bind hydrophobic polyolefins to hydrophilic lignocellulosic materials (e.g., wood or DDGS). The mechanical testing results of the effect of the coupling agent concentration are graphically presented in Figure 1.…”
Section: Influence Of Mapp Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix-filler interface plays a critical role in ensuring that the properties of each component contribute optimally to the properties of the final product, and is affected by a number of factors, including the nature of interfaces, the operational conditions (which may result in thermal degradation) and superficial chemical changes which could adversely affect the bulk properties [37,38]. For example, this type of effects has been reported by Takase and Shiraishi [39] in the co-extrusion of polypropylene and wood flour at 250ºC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The authors would like to thank the University Malaysia Sarawak (UNIMAS) for providing the sponsorship under FRGS research grant (UNIMAS/ FGRS/02(20)/741/2010 [27] that has made this work possible.…”
mentioning
confidence: 99%